#TITLE_ALTERNATIVE# - ANDRY (NIM: 10112021), ALFRED
During evacuation, a lot of life-threatening events are caused not by the disaster itself, but due to crowd’s behavior in panicked condition. This condition, which leads people to move faster than usual, pushing each other dan move together, may cause not only clogging near the exit but also toppling of pedestrians. To prevent such incidents in the future, construction of room interior need to consider the location and amount of exit doors relative to the number of people and their behavior during evacuation. For this study, the model that is used to represent crowd’s behavior during evacuation is Helbing’s model which is derived from particle’s behavior inside a vessel. The location that is chosen for this simulation is Mathematics Department of Institut Teknologi Bandung, which is located on the 4th and 5th floor of Central of Advanced Science (CAS). In order to generate more concrete simulation result, modifications are applied to the Helbing’s model. These modifications are: (1) pedestrians are capable to choose the desired exit by using the shortest route and (2) pedestrians are able to adjust theirs speed to the maximum allowed speed. For the simulation in which the maximum allowed speed is 3 meters per second, for the 4th floor case, there are 3 variations, which are: (1) pedestrians are assumed to be able to think rationally and able to choose the nearest exit, (2) pedestrians are assumed to be able to think rationally and able to head to the designated exit, and (3) pedestrians are assumed to not able to think rationally, which leads them to choose a random exit. The evacuation times fot the aforementioned variations are 19.13 seconds, 17.13 seconds and 32.84 seconds respectively. For the 5th floor case, there are 2 variations: (1) pedestrians are assumed to be able to think rationally and able to choose the nearest exit, with 3 available exits and (2) pedestrians are assumed to be able to think rationally and able to choose the nearest exit, with 2 available exits. The evacuation times for these 2 variations are respectively 35.91 seconds and 42.62 seconds. The conclusion obtained from this study is, evacuation becomes faster when: (1) pedestrians are able to think rationally during evacuation, (2) pedestrians are able to choose the exit that is not clogged, and (3) available exits are more abundant.